Association of Gestational Age with Verbal Ability and Spatial Working Memory at Age 11 - Fitzpatrick, A; Carter, J; Quigley, M (American Academy of Pediatrics, 2016)
Background. While children born very preterm (gestation <32 weeks) have an increased risk of cognitive impairment compared to full-term children (39-41 weeks), the risk for children born moderately (32-33 weeks) to late preterm (34-36 weeks) and early term (37-38 weeks) is unclear. This study describes the relationship between gestational age and cognitive outcomes at 11 years and the trajectory of deficits in verbal ability from age 3-11 years. Methods. Cognitive ability was assessed using the Spatial Working Memory Test from the Cambridge Neuropsychological Test Automated Working Battery (n=11,395) and British Ability Scale Verbal Similarities test (n=11,889) in the UK Millennium Cohort Study. Each gestational group was compared with the full-term group using differences in z-scores and odds ratios for delay (scoring ≥1 SD below the mean). Results. Very and moderately preterm children demonstrated significantly lower working memory scores compared to full-term children (adjusted difference -0.2 to -0.6) and were more likely to be delayed. There was no significant relationship between late preterm or early term birth and working memory (adjusted differences < -0.1), or between gestational age and verbal ability at 11 years. There appears to be a general attenuation in odds ratios as the child ages. Conclusion. Very preterm children exhibited working memory deficits at 11 years. However, the absence of delayed verbal skills at 11 years despite earlier delays could indicate ‘catch-up’ effects.